Inhibition of autophagy contributes to the toxicity of cadmium telluride quantum dots in Saccharomyces cerevisiae - Fan J (Dove Medical Press, 2016)
Junpeng Fan,1–4 Ming Shao,1–4 Lu Lai,3–5 Yi Liu,3–5 Zhixiong Xie1–4,6 1College of Life Sciences, Wuhan University, 2Hubei Provincial Cooperative Innovation Center of Industrial Fermentation,3State Key Laboratory of Virology, 4Key Laboratory of Analytical Chemistry for Biology and Medicine (MOE), 5College of Chemistry and Molecular Sciences, Wuhan University, Wuhan, 6School of Life Science and Technology, Hubei Engineering University, Xiaogan, People’s Republic of China Abstract: Cadmium telluride quantum dots (CdTe QDs) are used as near-infrared probes in biologic and medical applications, but their cytological effects and mechanism of potential toxicity are still unclear. In this study, we evaluated the toxicity of CdTe QDs of different sizes and investigated their mechanism of toxicity in the yeast Saccharomyces cerevisiae. A growth inhibition assay revealed that orange-emitting CdTe (O-CdTe) QDs (half inhibitory concentration [IC50] =59.44±12.02 nmol/L) were more toxic than green-emitting CdTe QDs (IC50 =186.61±19.74 nmol/L) to S. cerevisiae. Further studies on toxicity mechanisms using a transmission electron microscope and green fluorescent protein tagged Atg8 processing assay revealed that O-CdTe QDs could partially inhibit autophagy at a late stage, which differs from the results reported in mammalian cells. Moreover, autophagy inhibited at a late stage by O-CdTe QDs could be partially recovered by enhancing autophagy with rapamycin (an autophagy activator), combined with an increased number of living cells. These results indicate that inhibition of autophagy acts as a toxicity mechanism of CdTe QDs in S. cerevisiae. This work reports a novel toxicity mechanism of CdTe QDs in yeast and provides valuable information on the effect of CdTe QDs on the processes of living cells. Keywords: CdTe quantum dots, Saccharomyces cerevisiae, toxicity, autophagy